2022
DOI: 10.3390/medicina58050674
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Evaluation Using SRS-30 Score for Operated Children and Adolescent Idiopathic Scoliosis

Abstract: Background and objective: Adolescent idiopathic scoliosis (A.I.S.) is a disorder with a significant impact on health and self-image. This spinal deformity can affect between 2% and 4% of the adolescent population and may alter one’s quality of life. This study aims to assess the patient outcome, satisfaction, and quality of life following surgical treatment using the SRS-30 questionnaire. Materials and Methods: A number of 49 children and adolescent patients diagnosed with idiopathic scoliosis that had surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The following parameters were correlated with the SRS-30 results: [1] patient age at the time of surgery; [2] the use of braces before surgery; [3] the main thoracic Cobb angle; [4] the main thoracic curve correction; [5] patient gender and [6] complications.…”
Section: Cbc] Prothrombin Time [Pt] International Normalization Ratio...mentioning
confidence: 99%
See 3 more Smart Citations
“…The following parameters were correlated with the SRS-30 results: [1] patient age at the time of surgery; [2] the use of braces before surgery; [3] the main thoracic Cobb angle; [4] the main thoracic curve correction; [5] patient gender and [6] complications.…”
Section: Cbc] Prothrombin Time [Pt] International Normalization Ratio...mentioning
confidence: 99%
“…Additionally, the influence of the correction amount on functional outcomes of AIS is not well recognized. A weak correlation between curve of correction and functional outcomes was reported [4][5][6][7][8][9] . Also, another research showed a higher rate of complications after major corrections, comprising iatrogenic trunk imbalance [10] .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rapid correction of rigid curves can increase the risk of neurological complications [ 14 ], and traction can be a good orthopaedic technique for progressive deformity correction; scoliosis being one of the spine disorders for which it can be successfully applied, in an attempt to increase correction and minimize complications. An increase in patient satisfaction and quality of life was observed in cases with a high Cobb angle correction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%